PENERAPAN STRATEGI MARKETING DALAM UPAYA PERDAGANGAN KOPI DI PASAR INTERNASIONAL - Firly Agustiansyah; Destiana Destiana; Firda Nissa Apriliani (Jurnal Pijar, 2023)
The rapid development of world coffee production has led to an oversupply of world coffee resulting in tighter competition between producing countries and in the end prices tend to be depressed. This paper aims to examine the development of the world coffee market so that it can be considered in developing strategies and policy directions for Indonesian coffee commodities. Indonesia's coffee market share in traditional markets tends to decline, therefore efforts are needed, among others, to diversify destination markets and coffee products and increase exports of processed coffee. The results showed that the AEKI strategy was divided into 4 strategies, namely first approaching the Indonesian government to discuss coffee problems in Indonesia and new regulations issued by the United States and holding meetings in the United States to promote Indonesian coffee beans, secondly developing understanding. Regarding the regulation of coffee exports to coffee farmers in North Sumatra which is the most preferred type of coffee bean in the United States so that it has an impact on the products produced, the third is to improve the welfare of coffee farmers through the construction of an AEKI training center in Sumatra which will have an impact on the price of coffee beans, and fourthly increasing the productivity of Indonesian coffee which has an impact on distribution.